Endoscopic vacuum therapy in the late diagnosed iatrogenic esophageal perforation: The convenience of using fluoroscopy - Dişibeyaz, Selçuk; Öztaş, Erkin; Temel, Tuncer; Işıksalan Özbülbül, Nilgün (Turkish Journal of Gastroenterology, 2019)
Abstract Cite this article as: Dişibeyaz S, Öztaş E, Temel T, Işıksalan Özbülbül N. Endoscopic vacuum therapy in the late diagnosed iatrogenic esophageal perforation: The convenience of using fluoroscopy. Turk J Gastroenterol 2019; 30(7): 655-7.